Novel anthranilic amide derivatives bearing the chiral thioether and trifluoromethylpyridine: Synthesis and bioactivity. Issue 3 (1st February 2020) - Luo, Dexia; Guo, Shengxin; He, Feng; Wang, Heying; Xu, Fangzhou; Dai, Ali; Zhang, Renfeng; Wu, Jian
Graphical abstract: A series of anthranilic amide derivatives bearing the chiral thioether and trifluoromethyl pyridine was synthesized. Bioassays indicated the title compound showed good insecticidal and antiviral activity, such as compounds 5a, 5e and 5g had exhibited excellent insecticidal activity. Highlights: Ten novel chiral anthranilic amide derivatives were synthesized. Some of the synthesized compounds showed excellent insecticidal activity. Compounds 5b and 5e also showed excellent activity against TMV. Molecular docking on active compounds was discussed. Abstract: Ten anthranilic amides bearing skeletons of chiral thioether and trifluoromethylpyridine (5a-5j ) were designed and synthesized. Bioassays indicated that some of compounds had excellent insecticidal activity. For example, compounds 5a, 5e and 5g had the median lethal concentrations (LC50 ) against Plutella xylostella of 7.3, 8.7 and 8.1 µg/mL respectively. The LC50 of 5a against Ostrinia nubilalis and Pseudaletia separata were 21.7 and 44.2 µg/mL respectively. Anti-TMV tests indicated that some compounds also showed good antiviral activity. For instance, the curative activities of compounds 5b and 5e were 57.2% and 63.6%, and with half maximal effective concentration (EC50 ) of 304.5 and 203.0 µg/mL, respectively, which were much higher than these of ribavirin (39.4%, EC50 = 819.8 µg/mL) and ningnanmycin (56.2%, EC50 = 361.4 µg/mL). The molecular docking between the most active compounds and ryanodine receptor of the Plutella xylostella were also discussed. Those results indicated that the novel anthranilic amide derivatives in present work were worthy of further research and development as novel pesticides.